Application of multivariate statistical analysis to assess browning susceptibility in sweet potatoes (Ipomoea batatas (l.) Lam.) cultivars, based on chemical and enzymatic determinations - Ojeda, Gonzalo Adrián (2018)
Fil: Ojeda, Gonzalo Adrián. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.